Leontopolis: Kaiserstadt ohne Bischof? Lokalisierung und Geschichte einer isaurischen Märtyrer-Kultstätte - Pilhofer, Philipp (2021)
The city of Leontopolis in Isauria first appears in the sources towards the end of the 5th century, more precisely: in a legal text of the later Codex Iustinianus . In general, the surviving information is very sparse. In this essay, the source material is reviewed, in particular the mentioned law and the Martyrdom of Konon of Bidana. On this basis, a date of foundation is suggested, a new localisation of the city is established and the question of its own episcopal see is pursued.